Analisis Penggunaan Media Sosial (YouTube/TikTok) sebagai Media Pembelajaran Pendukung di Kalangan Pelajar Kelas XI SMAS Nurul Hasanah - Dian Syah Rani; Nadlrah Naimi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the use of social media, specifically YouTube and TikTok, as supporting learning media in Islamic Religious Education (PAI) at Nurul Hasanah Senior High School. The background of this research stems from the phenomenon of increasing social media use among adolescents, known as digital natives, and the potential of digital platforms as educational tools. The study used a descriptive qualitative approach, with eleventh-grade students and PAI teachers as subjects. Data collection techniques included interviews, observation, and documentation. The results showed that YouTube was effective in providing in-depth explanations of PAI material, while TikTok emphasized delivering short, motivational, and engaging messages in line with the characteristics of digital generation students. The use of social media has been proven to increase student motivation, participation, and understanding in PAI learning. However, challenges arise from distractions from non-learning content, limited information validity, and the potential for misuse of digital devices in schools. The role of teachers is crucial as facilitators, content curators, and supervisors to ensure the effective and responsible use of social media. Furthermore, school policies that allow students to bring mobile phones under certain conditions namely, collecting them when not in use and allowing them during lessons have been shown to balance the need for learning innovation with discipline. In conclusion, social media such as YouTube and TikTok can be effective supporting learning tools in Islamic Religious Education (PAI) when integrated with appropriate pedagogical strategies, teacher guidance, and school policy support.